Supramolecular deep eutectic conductive gel with microphase separation structure as well as preparation method and application of supramolecular deep eutectic conductive gel
By combining monomers such as N-(2-hydroxyethyl)acrylamide and [3-(methacrylamide)propyl]dimethyl(3-thiopropyl)ammonium hydroxide in the field of flexible electronics, supramolecular deep eutectic conductive gel with microphase separation structure was prepared, which solved the shortcomings of existing conductive gels in mechanical properties and conductivity, and achieved a high-performance conductive gel suitable for flexible electronic devices.
Patent Information
- Application Number
- CN202311209064.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-19
AI Technical Summary
The existing conductive gels based on deep eutectic solvents have poor mechanical properties and low conductivity in the field of flexible electronics, which cannot meet the basic needs of flexible electronic devices.
N-(2-hydroxyethyl)acrylamide and [3-(methacrylamide)propyl]dimethyl(3-thiopropyl)ammonium hydroxide were used as monomers, combined with choline chloride and ethylene glycol as deep eutectic solvents, and supramolecular deep eutectic conductive gel with a microphase separation structure was prepared by photopolymerization.
The prepared conductive gel has good mechanical properties and conductivity, high strength and good tensile properties, and can meet the needs of flexible electronic devices. Moreover, due to the use of green and non-toxic deep eutectic solvent, the preparation process is simple, the price is cheap and the environment is friendly.
Smart Images

Figure CN119661872A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive gels, and relates to a supramolecular deep eutectic conductive gel with a microphase separation structure, and a preparation method and application thereof. Background Art
[0002] With the rapid development of network communications and smart terminals, the updating of artificial intelligence and virtual reality technologies, people's demand for flexible electronic products with intelligence, lightness and personalization is increasing, and the field of flexible electronics shows broad application prospects. Compared with traditional electronic technology, flexible electronic devices have excellent stretchable and bendable properties, overcoming the basic defects of hard devices, and are widely used in wearable electronics, medical health, human-computer interaction and other aspects.
[0003] Conductive gels are widely used in flexible electronic devices due to their flexibility and conductivity. Hydrogels contain 70% to 80% water, which gives them excellent flexibility. However, water is not stable and is easy to evaporate or crystallize, causing hydrogels with water as a dispersion solvent to lose flexibility and fail, greatly limiting their application space. To solve the above problems, people introduced ionic liquid conductive gels, which use chemically stable, non-volatile ionic liquids as dispersion solvents. Since they do not contain water, they avoid the failure risk of similar hydrogels and improve the environmental stability of flexible electronic devices. However, ionic liquids are toxic and easily cause environmental pollution. In addition, the preparation process is complicated and expensive, which limits their market promotion and biocompatible applications. In contrast, deep eutectic solvents, as emerging green solvents, have physical properties similar to those of ionic liquids, such as low melting point, low vapor pressure, high conductivity, etc., and their raw materials are green, non-toxic and inexpensive (Hansen BB, Spittle S, Chen B, et al. Deep Eutectic Solvents: A Review of Fundamentals and Applications. Chem Rev. 2021; 121(3): 1232-1285.). However, at present, conductive gels prepared based on deep eutectic solvents still cannot meet the needs of the flexible electronics field. For example, Shu Hong et al. polymerized acrylamide in a deep eutectic solvent composed of choline chloride-urea-glycerol, and improved the mechanical properties of the gel by adding cellulose pulp to the dispersion system. However, even if a double network structure composed of polyacrylamide and cellulose was constructed, the mechanical properties were not significantly improved (the breaking strain was only 250% to 450%, and the tensile strength was 10 kPa to 60 kPa) due to the single form of intermolecular interaction in its internal network and the lack of covalent / non-covalent bond interactions (S. Hong, Y. Yuan, C. Liu, et al., A stretchable and compressible ion gel based on a deep eutectic solvent applied as a strain sensor and electrolyte for supercapacitors. J. Mater. Chem. C, 8 (2020), pp. 550-560).Ren'ai Li et al. used the method of copolymerization of hard segment (poly(acrylamide / choline chloride)) and soft segment (poly(acrylic acid / choline chloride)) to prepare deep eutectic gel. Due to the instability of the liquid system leading to irregular phase separation, the increase of soft segment will cause the soft domain to be trapped in the hard segment, while the increase of hard segment will cause the soft domain to shrink. Therefore, even if the ratio of soft and hard segments is tried to be adjusted, the gel as a whole still presents the characteristics of being hard and inextensible - the strength is high (65.74-108.13MPa), but the stretchability is only 5%-10%. At the same time, the densely entangled polymer chains limit the migration of ions, resulting in low conductivity of the gel (0.37-1.25*10. -3S / m). (Ren'ai Li, Kaili Zhang, Guangxue Chen, et al. Stiff, Self-Healable, Transparent Polymers with Synergetic Hydrogen Bonding Interactions. Chem. Mater. 2021, 33, 13, 5189-5196). JiLan et al. used choline chloride / ethylene glycol as a deep eutectic solvent to prepare a dual-network deep eutectic gel composed of physically cross-linked zwitterionic poly(3-dimethyl(methacryloyloxyethyl)propanesulfonate ammonium) (PDMAPS) and chemically cross-linked poly(2-hydroxyethyl methacrylate) (PHEMA), which improved the toughness of the gel to a certain extent (500%~1050%), but because the cross-linking mode of its internal polymer network is mainly weak physical cross-linking, its fracture strength is relatively low (100kPa~210kPa) (Lan, J., Zhou, B., Yin, C., Weng, L., Ni, W., & Shi, L. (2021). Zwitterionic dual-network strategy for highly stretchable and transparent ionic conductor.Polymer,231,124111.). In summary, the existing deep eutectic solvent-based gels have poor comprehensive mechanical properties and cannot meet the basic use requirements of flexible electronic devices. In addition, the deep eutectic gels prepared based on conventional polymer monomers have poor conductivity and impedance reaching the kilohm level, which cannot be used in flexible electronic devices (Ge G, Mandal K, Haghniaz R, et al. DeepEutectic Solvents-based Ionogels with Ultrafast Gelation and High Adhesion inHarsh Environments. Adv Funct Mater.2023;33(9):2207388.). Summary of the invention
[0004] The object of the present invention is to provide a supramolecular deep eutectic conductive gel with a microphase separation structure, and a preparation method and application thereof. The conductive gel uses N-(2-hydroxyethyl) acrylamide (HEAA) and [3-(methacrylamido)propyl] dimethyl (3-thiopropyl) ammonium hydroxide (SPP) as monomers, choline chloride and ethylene glycol as deep eutectic solvents (DeepEutectic Solvent, DES), and obtains the supramolecular deep eutectic conductive gel through photopolymerization. The positively and negatively charged groups on the SPP polyamphoteric monomers inside the supramolecular deep eutectic conductive gel can adsorb the polar deep eutectic solvent, thereby forming a soft phase inside the conductive gel, and the network formed by cross-linking the HEAA monomer forms a hard phase due to the lack of polar molecules, thereby preparing a conductive gel with a microphase separation structure. The deep eutectic solvent used in the conductive gel is formed by green and non-toxic choline chloride and ethylene glycol under the action of hydrogen bonds, and has good environmental stability and conductivity. The deep eutectic conductive gel contains abundant reversible non-covalent interactions such as hydrogen bonds, ionic bonds, van der Waals forces, and electrostatic effects, so the conductive gel has good self-healing, recovery, and fatigue resistance. The supramolecular deep eutectic conductive gel with a microphase separation structure of the present invention has a simple preparation process, low price, and environmental friendliness, and meets the various requirements for mechanical properties, environmental stability, and conductivity in flexible electronic applications, which can broaden the application space of flexible electronic devices and enrich application scenarios.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] The preparation method of supramolecular deep eutectic conductive gel with microphase separation structure uses N-(2-hydroxyethyl) acrylamide and [3-(methacrylamido)propyl] dimethyl (3-thiopropyl) ammonium hydroxide as monomers, uses deep eutectic solvent as a flexible dispersion solvent, and uses a photoinitiator to initiate free radical supramolecular polymerization cross-linking under ultraviolet light to form a conductive gel. The specific steps are as follows:
[0007] (1) dissolving choline chloride in ethylene glycol at a molar ratio of choline chloride to ethylene glycol of 1:2, heating and stirring until clear and transparent, and using the mixture as a deep eutectic solvent;
[0008] (2) adding N-(2-hydroxyethyl)acrylamide monomer and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide polyampholyl monomer into a deep eutectic solvent, and stirring until transparent and clear to obtain a precursor solution;
[0009] (3) Adding a photoinitiator to the precursor solution, stirring it evenly until it is transparent and clear, and then injecting it into a mold, where a polymerization reaction occurs under ultraviolet light to form a supramolecular deep eutectic conductive gel.
[0010] Preferably, in step (1), the heating temperature is 90-100° C. and the stirring speed is 800-1000 rpm.
[0011] Preferably, in step (2), the molar ratio of N-(2-hydroxyethyl)acrylamide to [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide is 8:1 to 10:1, more preferably 9:1.
[0012] Preferably, in step (2), the ratio of the total molar amount of choline chloride and ethylene glycol to the molar amount of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide is 5:1 to 8:1, more preferably 6:1.
[0013] In step (3), the photoinitiator is a photoinitiator conventionally used in the art. In a specific embodiment of the present invention, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is used as a representative example.
[0014] Preferably, in step (3), the mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 0.1% to 0.2% of the mass of the precursor solution.
[0015] Preferably, in step (2) or (3), the stirring speed is 800 to 1000 rpm.
[0016] Preferably, in step (3), the material of the mold is glass, and the interval between the molds is 900 to 1100 μm.
[0017] Preferably, in step (3), the wavelength of the ultraviolet light is 254 nm, and the intensity of the ultraviolet light is 800 μJ / cm 2 .
[0018] Preferably, in step (3), the polymerization reaction time is 30 minutes.
[0019] Furthermore, the present invention provides a supramolecular deep eutectic conductive gel prepared by the above preparation method.
[0020] Furthermore, the present invention provides the use of the supramolecular deep eutectic conductive gel in the preparation of flexible electronic devices.
[0021] The flexible electronic devices described in the present invention include but are not limited to flexible sensors and flexible wearable sensors.
[0022] The flexible sensor and the flexible wearable sensor described in the present invention are composed of the above-mentioned supramolecular deep eutectic conductive gel and copper sheet electrodes and adhesive tapes attached to both sides of the electrolyte.
[0023] Preferably, the adhesive tape is VHB tape.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The present invention utilizes choline chloride to form hydrogen bonds with hydroxyl groups in ethylene glycol to produce a eutectic effect, thereby lowering the melting point of choline chloride, and preparing a deep eutectic solvent with low vapor pressure, low glass transition temperature, green and pollution-free and conductive. Therefore, the prepared conductive gel has good environmental stability (working temperature range: -64 to 192°C) and conductivity (ionic conductivity is 0.02S / m).
[0026] (2) The present invention utilizes the polyamphoteric monomer [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to adsorb polar molecules in the deep eutectic solvent to form a soft phase. N-(2-hydroxyethyl)acrylamide forms a hard phase due to the absence of a dispersing solvent, thereby constructing a microphase separation structure inside the conductive gel. The interaction between the soft and hard phases provides an effective energy dissipation mechanism, thereby improving the comprehensive mechanical properties of the conductive gel, which has both high strength and good tensile strength, and reflects toughened mechanical properties.
[0027] (3) The polyamphoteric monomer [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide used in the present invention has both positively charged groups and negatively charged groups on one monomer molecule, which can not only adsorb polar molecules in deep eutectic solvents, but also cooperate with deep eutectic solvents to improve the conductivity of conductive gels. The ionic conductivity reaches 0.02 to 0.07 S / m, which is at the same level as expensive and toxic ionic liquid gels.
[0028] (4) The supramolecular deep eutectic conductive gel of the present invention contains a large number of reversible non-covalent physical interactions such as hydrogen bonds, ionic bonds, electrostatic interactions and van der Waals forces. These physical interactions can be quickly and randomly reconstructed, so that the internal network of the conductive gel has good recovery performance and fatigue resistance: after being stretched to a strain of 500%, unloaded to a strain of 0% and left to stand at room temperature for 5 minutes, 92% of the mechanical properties (dissipated energy) can be recovered. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The stress-strain curves of the supramolecular deep eutectic conductive gels prepared in Examples 1, 2, and 3;
[0030] Figure 2 The stress-strain curves of the supramolecular deep eutectic conductive gels prepared in Examples 1, 5, and 6;
[0031] Figure 3 The loading-unloading cyclic tensile stress-strain curve of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0032] Figure 4 The energy dissipation bar graph and the self-recovery efficiency line graph calculated by the loading-unloading cyclic stretching of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0033] Figure 5 The stress-strain curves of the supramolecular deep eutectic conductive gel prepared in Example 1 and the deep eutectic gel prepared in Comparative Example 1;
[0034] Figure 6 This is a scanning electron microscope image of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0035] Figure 7 The impedance spectrum of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0036] Figure 8 This is a thermogravimetric analysis diagram of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0037] Fig. 9 is a differential scanning calorimetry image of the supramolecular deep eutectic conductive gel prepared in Example 1;
[0038] Fig.10 The response diagram of the flexible sensor based on supramolecular deep eutectic conductive gel to stretching stimulation;
[0039] Fig.11 The response diagram of the flexible sensor based on supramolecular deep eutectic conductive gel to pressure stimulation;
[0040] Fig.12 The response diagram of the flexible sensor based on supramolecular deep eutectic conductive gel to bending stimulation;
[0041] Fig.13 The response signal diagram of the flexible sensor based on supramolecular deep eutectic conductive gel to 500 cycles of stretching test;
[0042] Fig.14 The response signal diagram of the flexible wearable sensor based on supramolecular deep eutectic conductive gel to the movement of human shoulder joint;
[0043] Fig.15 The response signal diagram of the flexible wearable sensor based on supramolecular deep eutectic conductive gel to the movement of the human elbow joint;
[0044] Fig.16 This is the response signal diagram of the flexible wearable sensor based on supramolecular deep eutectic conductive gel to human knee joint movement. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0046] Example 1: Preparation of supramolecular deep eutectic conductive gel with microphase separation structure (the molar ratio of monomers HEAA:SPP is 9:1, and the molar ratio of polar molecules (cations and anions in choline chloride and ethylene glycol) to SPP is 6:1)
[0047] (1) Weigh 0.3006 g of choline chloride into a 5 mL sample bottle, then pipette 0.24 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0048] (2) Add 0.3134 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to the above deep eutectic solvent, then draw 1 mL of N-(2-hydroxyethyl)acrylamide and dropwise add it into the sample bottle, stir at room temperature until it becomes clear and transparent, to obtain a conductive gel precursor solution.
[0049] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain a supramolecular deep eutectic conductive gel.
[0050] Example 2: Preparation of supramolecular deep eutectic conductive gel with microphase separation structure (monomer molar ratio HEAA:SPP is 9:1, polar molecule to SPP molar ratio is 5:1)
[0051] (1) Weigh 0.2487 g of choline chloride into a 5 mL sample bottle, then pipette 0.1986 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0052] (2) Add 0.3134 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to the above deep eutectic solvent, then draw 1 mL of N-(2-hydroxyethyl)acrylamide and dropwise add it into the sample bottle, stir at room temperature until it becomes clear and transparent, to obtain a conductive gel precursor solution.
[0053] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain a supramolecular deep eutectic conductive gel.
[0054] Example 3: Preparation of supramolecular deep eutectic conductive gel with microphase separation structure (molar ratio of monomers HEAA:SPP is 9:1, molar ratio of polar molecules to SPP is 8:1)
[0055] (1) Weigh 0.3972 g of choline chloride into a 5 mL sample bottle, then pipette 0.3173 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0056] (2) Add 0.3134 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to the above deep eutectic solvent, then draw 1 mL of N-(2-hydroxyethyl)acrylamide and dropwise add it into the sample bottle, stir at room temperature until it becomes clear and transparent, to obtain a conductive gel precursor solution.
[0057] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain a supramolecular deep eutectic conductive gel.
[0058] Example 4: Mechanical properties test of supramolecular deep eutectic conductive gel with microphase separation structure
[0059] The mechanical properties of the supramolecular deep eutectic conductive gels prepared in Examples 1 to 3 were tested. The stress-strain curves of the conductive gels with different molar ratios of polar molecules to SPP in the deep eutectic solvent were as follows: Figure 1As shown. When the molar ratio of polar molecules to SPP is 5:1, the conductive gel with a microphase separation structure uses the coordination of soft and hard phases to show a higher elastic modulus (5.12MPa) and strength (fracture strength of 5.38MPa), and maintains a good elongation at break (824%). When the molar ratio of polar molecules to SPP is 6:1, the ability of SPP to adsorb polar molecules reaches saturation, and the conductive gel shows good comprehensive mechanical properties, which can meet the needs of various flexible electronic devices. Its elongation at break is 1097% and its fracture stress is 936.8kPa. As the content of polar molecules is further increased, when the molar ratio of polar molecules to SPP reaches 8:1, due to the saturation of SPP adsorption capacity, the excess deep eutectic solvent is evenly dispersed between the HEAA polymer network, weakening the microphase separation structure, so the conductive gel is in a softer state, with elastic modulus and fracture strength of 51kPa and 100kPa respectively, but the elongation at break is greatly improved (2111%). Therefore, the conductive gel prepared in Example 3 is suitable for flexible electronic devices used under large strain conditions. In summary, the conductive gel prepared in Example 1 (the molar ratio of polar molecules to SPP is 6:1) has the best comprehensive mechanical properties.
[0060] Example 5: Preparation of supramolecular deep eutectic conductive gel with microphase separation structure (monomer molar ratio HEAA:SPP is 8:1, polar molecule to SPP molar ratio is 6:1)
[0061] (1) Weigh 0.3368 g of choline chloride into a 5 mL sample bottle, then pipette 0.2690 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0062] (2) Add 0.3526 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to the above deep eutectic solvent, then draw 1 mL of N-(2-hydroxyethyl)acrylamide and dropwise add it into the sample bottle, stir at room temperature until it becomes clear and transparent, to obtain a conductive gel precursor solution.
[0063] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain a supramolecular deep eutectic conductive gel.
[0064] Example 6: Preparation of supramolecular deep eutectic conductive gel with microphase separation structure (monomer molar ratio HEAA:SPP is 10:1, polar molecule to SPP molar ratio is 6:1)
[0065] (1) Weigh 0.2700 g of choline chloride into a 5 mL sample bottle, then pipette 0.2157 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0066] (2) Add 0.2821 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide to the above deep eutectic solvent, then draw 1 mL of N-(2-hydroxyethyl)acrylamide and dropwise add it into the sample bottle, stir at room temperature until it becomes clear and transparent, to obtain a conductive gel precursor solution.
[0067] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain a supramolecular deep eutectic conductive gel.
[0068] Example 7: Mechanical properties test of supramolecular deep eutectic conductive gel with microphase separation structure
[0069] The mechanical properties of the supramolecular deep eutectic conductive gels prepared in Examples 1, 5, and 6 were tested. The stress-strain curves of the conductive gels with different molar ratios of N-(2-hydroxyethyl)acrylamide (HEAA) and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide (SPP) were measured as follows: Figure 2 As shown. When the molar ratio of HEAA to SPP monomer is 10:1, compared with Example 1, the increase in the proportion of HEAA content increases the proportion of hard phase in the conductive gel, showing an ultra-high elastic modulus of 6.28MPa. When the molar ratio of HEAA to SPP monomer is 8:1, compared with Example 1, the increase in the proportion of SPP content increases the proportion of soft phase in the conductive gel, and the elastic modulus is reduced to 0.14MPa. Due to the lack of effective support of the hard phase, the elongation at break will be 552%. In summary, the conductive gel prepared in Example 2 with a molar ratio of HEAA to SPP monomer of 9:1 has the best comprehensive mechanical properties.
[0070] Example 8: Loading-unloading cyclic tensile test of supramolecular deep eutectic conductive gel with microphase separation structure
[0071] The supramolecular deep eutectic conductive gel prepared in Example 1 was subjected to a loading-unloading cyclic stretching test. The conductive gel was first stretched to a strain of 500%, and then unloaded to a strain of 0%, as the first cyclic stretching. Immediately thereafter, the same loading-unloading cyclic stretching test was performed again, and then the same loading-unloading cyclic stretching test was performed at intervals of 1 minute, 3 minutes, and 5 minutes, respectively. The stress-strain curves obtained by the test are shown in FIG. Figure 3As shown. As can be seen from the figure, with the increase of static time, the loading curve gradually approaches the initial curve, indicating that the conductive gel has self-recovering resilience in mechanical properties. This is because the conductive gel has a large number of reversible non-covalent interactions such as hydrogen bonds, ionic bonds, van der Waals forces, and electrostatic interactions. These physical interactions can provide an effective energy dissipation mechanism when loaded, and can be quickly rebuilt when unloading and static, which manifests as the recovery of the mechanical properties of the conductive gel on a macro scale. Integrate each loading-unloading cycle curve to obtain the energy dissipated during each cyclic stretching process (the work done during the stretching process) as shown in the figure. Figure 4 As shown in the figure, even if it is loaded again immediately, the energy dissipated by the conductive gel during cyclic stretching still accounts for 66% of the initial energy. After standing for 5 minutes, this proportion increases to 92%, showing excellent resilience.
[0072] Comparative Example 1: Preparation of N-(2-hydroxyethyl)acrylamide deep eutectic gel (HEAA-DES)
[0073] (1) Weigh 0.3006 g of choline chloride into a 5 mL sample bottle, then pipette 0.24 mL of ethylene glycol and dropwise add it into the sample bottle, heat and stir at 95° C. for 2 hours until the solution becomes clear and transparent, and let stand to room temperature to obtain a deep eutectic solvent.
[0074] (2) Add 1 mL of N-(2-hydroxyethyl)acrylamide to the deep eutectic solvent and dropwise add the mixture into a sample bottle, and stir at room temperature until the mixture becomes clear and transparent to prepare a conductive gel precursor solution.
[0075] (3) Add 20 mg of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the above precursor solution, stir until transparent and clear, and then inject into a glass mold. In a UV crosslinker (254 nm), photopolymerize for 30 minutes to obtain N-(2-hydroxyethyl) acrylamide deep eutectic gel.
[0076] Comparative Example 2: Preparation of [3-(Methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide deep eutectic gel (SPP-DES)
[0077] This comparative example is basically the same as Example 1, except that only [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide is added and N-(2-hydroxyethyl)acrylamide is not added. Under this condition, gelation cannot be achieved.
[0078] Example 9: Validity test of microphase separation structure of supramolecular deep eutectic conductive gel
[0079] The supramolecular deep eutectic conductive gel prepared in Example 1 and the deep eutectic gel prepared in Comparative Example 1 were subjected to uniaxial tensile mechanical property tests. The results are as follows: Figure 5As shown. Example 1 and Comparative Example 1 contain the same amount of deep eutectic solvent. Since the addition of SPP in Example 1 triggers the microphase separation structure inside the conductive gel, the mechanical properties of Example 1 are significantly better than those of Comparative Example 1, proving the existence and effectiveness of the microphase separation structure. Further, the surface of the conductive gel prepared in Example 1 was sprayed with gold and observed under a scanning electron microscope at a magnification of 10,000 times. The electron microscope picture is as follows Figure 6 As shown, a microphase separation structure with obvious light and dark distinction can be observed in the figure, proving the existence of the microphase separation structure.
[0080] Example 10: Conductivity test of supramolecular deep eutectic conductive gel with microphase separation structure
[0081] The supramolecular deep eutectic conductive gel prepared in Example 1 was placed in an electrolyte impedance test mold and scanned in the frequency range of 100 kHz to 1 Hz to obtain the impedance spectrum of Example 1 as shown in FIG. Figure 7 As shown, the size of the conductive gel was measured and the ionic conductivity of the conductive gel was calculated to be 0.02S / m. This ionic conductivity is at the same order of magnitude as the conductivity of the ionic liquid gel and can meet the use requirements of most flexible electronic devices.
[0082] Example 11: Environmental stability test of supramolecular deep eutectic conductive gel with microphase separation structure
[0083] The supramolecular deep eutectic conductive gel prepared in Example 1 was subjected to thermogravimetric analysis and differential scanning calorimetry analysis. The results are as follows: Figure 8 , 9 As shown. From the thermogravimetric analysis graph, it can be seen that before 192°C, the conductive gel has no obvious mass loss, indicating that the conductive gel has almost no decomposition reaction before 192°C. From the differential scanning calorimetry graph, it can be seen that no glass transition occurs when the temperature drops from room temperature to -62°C, and the conductive gel always remains flexible.
[0084] Application Example 1: Preparation of flexible sensors and testing of their mechanical sensing performance
[0085] Copper wire electrodes were attached to both sides of the supramolecular deep eutectic conductive gel prepared in Example 1, and then packaged with VHB elastic tape to assemble a flexible sensor. The responses of the flexible sensor to three stimulation signals, namely, stretching, pressing, and bending, were tested. The test results are shown in Figure 2. Fig.10 , 11 , 12. The results show that the flexible sensor responds accurately, sensitively and stably to the three stimulation signals of stretching, pressing and bending.
[0086] Application Example 2: Fatigue Test of Flexible Sensors
[0087] The flexible sensor prepared in Application Example 1 was installed on a cyclic stretching instrument, and 500 cyclic stretching stimuli with the same strain were applied to the flexible sensor. The test results are as follows: Fig.13 Because the supramolecular deep eutectic conductive gel that constitutes the flexible sensor has good resilience, the test results show that the flexible sensor still maintains accurate and sensitive response after 500 cycles of stretching.
[0088] Application Example 3: Testing of Flexible Wearable Sensors
[0089] The flexible sensor prepared in Application Example 1 was attached to the main joints of the human body to test the response of the flexible wearable sensor to different joint activities of the human body. The test results are as follows: Fig.14 , 15 As shown in Figures 16, the resistive strain sensor has a comprehensive and accurate response to the basic movements of human joints, and is expected to expand the application of the wearable sensor in medical rehabilitation, motion monitoring, human-computer interaction and other fields.
[0090] The above descriptions are merely embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a supramolecular deep eutectic conductive gel having a microphase separation structure, characterized in that: The specific steps are as follows: (1) dissolving choline chloride in ethylene glycol at a molar ratio of choline chloride to ethylene glycol of 1:2, heating and stirring until the solution becomes clear and transparent, and using this as a deep eutectic solvent; (2) Adding N-(2-hydroxyethyl)acrylamide monomer and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide polyampholyl monomer into a deep eutectic solvent, and stirring evenly until transparent and clear to prepare a precursor solution; (3) Add a photoinitiator to the precursor solution, stir it until it is transparent and clear, and then inject it into the mold. Under ultraviolet light, a polymerization reaction occurs to form a supramolecular deep eutectic conductive gel.
2. The preparation method according to claim 1, characterized in that In step (1), the heating temperature is 90-100° C. and the stirring speed is 800-1000 rpm.
3. The preparation method according to claim 1, characterized in that In step (2), the molar ratio of N-(2-hydroxyethyl)acrylamide to [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide is 8:1 to 10:1, preferably 9:1; the ratio of the total molar amount of choline chloride and ethylene glycol to the molar amount of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide is 5:1 to 8:1, more preferably 6:
1.
4. The preparation method according to claim 1, characterized in that: The photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and the mass of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is 0.1% to 0.2% of the mass of the precursor solution.
5. The preparation method according to claim 1, characterized in that In step (2) or (3), the stirring speed is 800-1000 rpm; in step (3), the mold is made of glass, the mold interval is 900-1100 μm, the wavelength of the ultraviolet light is 254 nm, and the ultraviolet light irradiation intensity is 800 μJ / cm 2 , the polymerization reaction time is 30 minutes.
6. The supramolecular deep eutectic conductive gel prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the supramolecular deep eutectic conductive gel according to claim 6 in the preparation of flexible electronic devices.
8. The use according to claim 7, characterized in that: The flexible electronic device is a flexible sensor or a flexible wearable sensor.
9. The use according to claim 8, characterized in that: The flexible sensor or flexible wearable sensor is composed of a supramolecular deep eutectic conductive gel and copper sheet electrodes and tapes attached to both sides of an electrolyte.
10. The use according to claim 9, characterized in that: The adhesive tape is a VHB tape.
Citation Information
Patent Citations
Self-adhesive conductive gel and preparation method thereof
CN114349899A
Flexible polyion eutectic gel as well as preparation method and application thereof
CN115340631A
Self-healing stretchable eutectic gel electrode and preparation method and application thereof
CN115663185A
Eutectoid gel with biosensing performance and antibacterial effect and preparation method of eutectoid gel
CN116217980A
Cited By
Miniature flexible temperature sensor for living body, preparation method and application thereof
CN122237795A